nakalimutan ko na eh,, -_-

Factor -.- .. Hate it lol

Ok i'll try :)

Log in to add a comment

nakalimutan ko na eh,, -_-

Factor -.- .. Hate it lol

Ok i'll try :)

Log in to add a comment

The Brainliest Answer!

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

1) x² + 7x = 0

x(x+7) = 0

x=0 ; x=-7

2) 6s² + 18s = 0

6s(s+3) = 0

s=0 ; s=-3

3) t² + 8t + 16 = 0

(t+4)(t+4) = 0

t=4

4) x² -10x +25 = 0

(x-5)(x-5) = 0

x=5

5) h² +6h =16

h² +6h -16 = 0

(h+8)(h-2) = 0

h=-8 ; h=2

6) x² -5x -14 = 0

(x-7)(x+2) = 0

x=7 ; x=-2

7) 11r +15 = -2r²

2r² +11r +15 = 0

(2r+5)(r+3)= 0

r=-5/2 ; r=3

8) x² -25 = 0

(x-5)(x+5)=0

x=5 ; x=-5

9) 81 - 4x² = 0

(9-2x)(9+2x)=0

x=9/2 ; x=-9/2

10) 4s² +9 = 12s

4s² -12s +9=0

(2s-3)(2s-3)=0

s=3/2

d) by equating all the factors to 0

e) Zero product property. Since each of the polynomials may be equated to 0, then at least of their factors is equal to 0.

x(x+7) = 0

x=0 ; x=-7

2) 6s² + 18s = 0

6s(s+3) = 0

s=0 ; s=-3

3) t² + 8t + 16 = 0

(t+4)(t+4) = 0

t=4

4) x² -10x +25 = 0

(x-5)(x-5) = 0

x=5

5) h² +6h =16

h² +6h -16 = 0

(h+8)(h-2) = 0

h=-8 ; h=2

6) x² -5x -14 = 0

(x-7)(x+2) = 0

x=7 ; x=-2

7) 11r +15 = -2r²

2r² +11r +15 = 0

(2r+5)(r+3)= 0

r=-5/2 ; r=3

8) x² -25 = 0

(x-5)(x+5)=0

x=5 ; x=-5

9) 81 - 4x² = 0

(9-2x)(9+2x)=0

x=9/2 ; x=-9/2

10) 4s² +9 = 12s

4s² -12s +9=0

(2s-3)(2s-3)=0

s=3/2

d) by equating all the factors to 0

e) Zero product property. Since each of the polynomials may be equated to 0, then at least of their factors is equal to 0.